Polyethylene-based resin multilayer extrusion foam sheet for thermoforming, molding, and method for producing polyethylene-based resin multilayer extrusion foam sheet for thermoforming

The polyethylene resin multilayer extruded foam sheet, with optimized foam and resin layers, addresses thermoformability and rigidity issues, enabling better molding performance and rigid article production.

JP2025006961APending Publication Date: 2025-01-17JSP CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023108035
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing polyethylene resin extruded foam sheets for thermoforming have limitations in thermoformability and rigidity of the molded articles, necessitating improvements for better performance.

Method used

A polyethylene resin multilayer extruded foam sheet is developed with a foam layer composed of branched low-density polyethylene and a resin layer composed of specific polyethylene resin compositions, optimized for crystallization temperatures and tensile properties, to enhance thermoformability and rigidity.

Benefits of technology

The multilayer extruded foam sheet achieves improved thermoformability and rigidity, allowing for wider molding ranges and the production of high-quality, rigid molded articles even with thin thickness or small basis weight.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025006961000013
    Figure 2025006961000013
  • Figure 2025006961000001
    Figure 2025006961000001
  • Figure 2025006961000002
    Figure 2025006961000002
Patent Text Reader

Abstract

To provide a polyethylene-based resin multilayer extrusion foam sheet for thermoforming which has good thermoformability and can improve rigidity, a molding, and a method for producing a polyethylene-based resin multilayer extrusion foam sheet for thermoforming.SOLUTION: In a polyethylene-based resin multilayer extrusion foam sheet for thermoforming in which a polyethylene-based resin layer is laminated on at least one surface side of a polyethylene-based resin foam layer containing branched low density polyethylene as a main component, a crystallization temperature Tcr of the polyethylene-based resin composition constituting the polyethylene-based resin layer is 108°C or lower, and a product of tensile strength (MPa) and tensile elongation (%) at 110°C of the polyethylene-based resin composition constituting the polyethylene-based resin layer is 1,300 (MPa %) or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a multi-layer extruded polyethylene resin foam sheet for thermoforming, a molded article obtained by thermoforming the multi-layer extruded polyethylene resin foam sheet for thermoforming, and a method for producing the multi-layer extruded polyethylene resin foam sheet for thermoforming. [Background technology]

[0002] A polyethylene-based resin extrusion foam sheet for thermoforming can be shaped into a packaging container or the like by thermoforming, and is used in a wide range of applications such as cushioning material. As a polyethylene-based resin extrusion foam sheet for thermoforming, Patent Document 1 proposes a multi-layer polyethylene resin extrusion foam sheet for thermoforming from the viewpoint of improving thermoformability. The multi-layer polyethylene resin extrusion foam sheet for thermoforming proposed in Patent Document 1 has a polyethylene resin foam layer and a polyethylene resin layer on its surface, and a linear polyethylene resin is blended so that the polyethylene resin layer shows a specific heat of fusion. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2013-35177 A Summary of the Invention [Problem to be solved by the invention]

[0004] Although the extruded polyethylene resin foam sheet for thermoforming obtained by the technique of Patent Document 1 has a suitable thermoformability, there is room for further improvement in terms of obtaining a higher level of thermoformability. Also, there is room for further improvement in terms of the rigidity of the molded article obtained by thermoforming the extruded polyethylene resin foam sheet for thermoforming.

[0005] An object of the present invention is to provide a multi-layer extruded polyethylene resin foam sheet for thermoforming which has good thermoformability and can improve rigidity, a molded product obtained by thermoforming the multi-layer extruded polyethylene resin foam sheet for thermoforming, and a method for producing the multi-layer extruded polyethylene resin foam sheet for thermoforming. [Means for solving the problem]

[0006] The present invention relates to the following (1) to (13).

[0007] (1) A multi-layer extruded polyethylene-based resin foam sheet for thermoforming, comprising a polyethylene-based resin layer laminated on at least one side of a polyethylene-based resin foam layer mainly composed of a branched low-density polyethylene, wherein the crystallization temperature Tcr of the polyethylene-based resin composition constituting the polyethylene-based resin layer is 108°C or lower, The polyethylene-based resin multi-layer extruded foam sheet for thermoforming, wherein the product of tensile strength (MPa) and tensile elongation (%) at 110°C of the polyethylene-based resin composition constituting the polyethylene-based resin layer is 1,300 (MPa %) or more. (2) The multi-layer extruded polyethylene-based resin foam sheet for thermoforming according to the above (1), wherein a difference [Tcr-Tcf] between a crystallization temperature Tcf of the branched low-density polyethylene and a crystallization temperature Tcr of the polyethylene-based resin composition is 0°C or more and 10°C or less. (3) The multi-layer extruded polyethylene resin foam sheet for thermoforming according to the above (1) or (2), wherein the thickness of the multi-layer extruded polyethylene resin foam sheet for thermoforming is 1 mm or more and 3.5 mm or less. (4) The basis weight of the polyethylene-based resin multi-layer extruded foam sheet for thermoforming is 150 g / m 2 The multi-layer extruded polyethylene resin foam sheet for thermoforming according to any one of the above (1) to (3), which is: (5) The multi-layer extruded polyethylene-based resin foam sheet for thermoforming according to any one of the above (1) to (4), wherein the polyethylene-based resin composition contains a linear low-density polyethylene. (6) The multi-layer extruded polyethylene resin foam sheet for thermoforming according to any one of the above (1) to (4), wherein the polyethylene resin composition comprises a mixed resin of linear low-density polyethylene and branched low-density polyethylene as a main component, and a mass ratio of the linear low-density polyethylene to the branched low-density polyethylene in the polyethylene resin composition is 90:10 to 30:70. (7) The multi-layer extruded polyethylene-based resin foam sheet for thermoforming according to any one of the above (1) to (6), wherein a ratio of tensile elongation (%) of the polyethylene-based resin composition at 110°C to tensile elongation (%) of the polyethylene-based resin composition at 23°C is 0.3 or more. (8) The polyethylene-based resin multi-layer extruded foam sheet for thermoforming according to any one of the above (1) to (7), wherein the polyethylene-based resin composition contains one or more shrinkage inhibitors selected from the group consisting of fatty acid esters, aliphatic amines, and fatty acid amides, the blending amount of the shrinkage inhibitor being 0.7 parts by mass or more and 3 parts by mass or less per 100 parts by mass of the polyethylene-based resin constituting the polyethylene-based resin composition, and the polyethylene-based resin foam layer is substantially free of one or more shrinkage inhibitors selected from the group consisting of fatty acid esters, aliphatic amines, and fatty acid amides. (9) The multi-layer extruded polyethylene-based resin foam sheet for thermoforming according to any one of the above (1) to (8), wherein the product of tensile strength (MPa) and tensile elongation (%) at 110°C of the polyethylene-based resin composition is 1600 or more, and the polyethylene-based resin foam layer and the polyethylene-based resin layer are substantially free of one or more shrinkage inhibitors selected from the group consisting of fatty acid esters, aliphatic amines, and fatty acid amides. (10) The multi-layer extruded polyethylene-based resin foam sheet for thermoforming according to any one of the above (1) to (4) and (6) to (9), wherein the polyethylene-based resin composition contains a copolymer of ethylene and an α-olefin having 8 carbon atoms as the linear low-density polyethylene. (11) The multi-layer extruded polyethylene-based resin foam sheet for thermoforming according to any one of the above (1) to (10), wherein the multi-layer extruded polyethylene-based resin foam sheet for thermoforming has a closed cell ratio of 40% or more. (12) A molded article obtained by thermoforming the multi-layer extruded polyethylene resin foam sheet for thermoforming according to any one of (1) to (11) above. (13) Co-extruding a melt for forming a foam layer obtained by kneading a branched low-density polyethylene and a physical foaming agent and a melt for forming a resin layer obtained by melt-kneading a polyethylene-based resin composition, A method for producing a multi-layer extruded polyethylene resin foam sheet for thermoforming, in which a polyethylene resin layer is laminated on at least one side of a polyethylene resin foam layer, comprising the steps of: The crystallization temperature Tcr of the polyethylene resin composition is 108° C. or lower, The polyethylene resin composition has a product of tensile strength (MPa) and tensile elongation (%) at 110°C of 1300 (MPa·%) or more. Effect of the Invention

[0008] According to the present invention, there are provided a multi-layer extruded polyethylene resin foam sheet for thermoforming which has good thermoformability and can improve rigidity, a molded product obtained by thermoforming the multi-layer extruded polyethylene resin foam sheet for thermoforming, and a method for producing the multi-layer extruded polyethylene resin foam sheet for thermoforming. [Brief description of the drawings]

[0009] [Figure 1] Fig. 1A is a graph showing an example of a DSC curve of a resin composition (A), and Fig. 1B is a graph showing an example of a DSC curve of a resin composition (B). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] An example of an embodiment of the present invention will be described below. Note that the present invention is not limited to the embodiment described below.

[0011] [1. Polyethylene resin multi-layer extruded foam sheet for thermoforming] The multi-layer extruded polyethylene resin foam sheet for thermoforming (hereinafter referred to as the multi-layer extruded foam sheet) of the present invention is a multi-layer extruded foam sheet in which a polyethylene resin layer (hereinafter referred to as the resin layer) is laminated on at least one side of a polyethylene resin foam layer (hereinafter referred to as the foam layer). The multi-layer extruded foam sheet according to the present invention may have a resin layer formed on at least one side of the foam layer, but may have resin layers formed on both sides of the foam layer. From the viewpoint of making the effect of the resin layer described later predominant and obtaining a multi-layer foam sheet with better thermoformability, it is preferable that the resin layer is laminated on both sides of the foam layer. It is preferable that the foam layer and the resin layer are laminated and bonded by co-extrusion. However, an intermediate layer may be provided between the foam layer and the resin layer.

[0012] (Foam layer) The foam layer is made of a resin composition (foam layer-forming resin composition) mainly composed of branched low density polyethylene. Therefore, the foam layer mainly comprises branched low density polyethylene. In this specification, the foam layer-forming resin composition, which is the resin composition that forms the foam layer, may be referred to as resin composition (A).

[0013] (Branched low density polyethylene) In this specification, the branched low density polyethylene is generally called low density polyethylene (sometimes abbreviated as PE-LD or LDPE), has long chain branches, and has a density of 910 kg / m 3 More than 930kg / m 3 The melting point (°C) of the branched low density polyethylene is preferably 95°C or higher and 120°C or lower, and more preferably 100°C or higher and 115°C or lower, from the viewpoints of extrusion foamability, cushioning properties, etc.

[0014] In the present specification, the term "mainly composed" of a specific component in a composition means that the content of the specific component in 100% by mass of the composition is 50% by mass or more. Specifically, the term "mainly composed of branched low density polyethylene" in the resin composition (A) means that the content of branched low density polyethylene in the resin composition (A) is 50% by mass or more. When the resin composition (A) contains branched low density polyethylene as a main component, that is, when the foam layer contains branched low density polyethylene as a main component, the cushioning properties of the multi-layer extrusion foam sheet and the cushioning properties of the molded article obtained by thermoforming the multi-layer extrusion foam sheet can be improved. From the viewpoint of such cushioning properties, the content of branched low density polyethylene in the resin composition (A) is preferably 60% by mass or more.

[0015] (Other polyethylene resins) The resin composition (A) may contain other polyethylene-based resins different from the branched low-density polyethylene. The polyethylene-based resin refers to an ethylene homopolymer or an ethylene copolymer containing 50% by mass or more of an ethylene component. Examples of other polyethylene-based resins include linear low-density polyethylene and high-density polyethylene. However, from the viewpoint of ensuring sufficient cushioning properties of the multi-layer extruded foam sheet, the content of high-density polyethylene is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 0% by mass, that is, the resin composition (A) does not contain high-density polyethylene, based on 100% by mass of the resin composition (A). In the present specification, high-density polyethylene refers to an ethylene homopolymer or a copolymer of ethylene and an α-olefin having 4 to 8 carbon atoms, and has a density of 930 kg / m 3 This refers to the above polyethylene.

[0016] (Linear low density polyethylene) Among them, it is preferable that the resin composition (A) contains linear low density polyethylene. When the resin composition (A) contains linear low density polyethylene, the heat resistance of the foam layer can be improved, and the thermoformability of the multi-layer extruded foam sheet can be further improved. In addition, the adhesion between the foam layer and the resin layer can be improved. In this specification, linear low density polyethylene is a copolymer of ethylene and an α-olefin having 4 to 8 carbon atoms, has a substantially linear molecular chain, and has a density of usually 910 kg / m 3 More than 930kg / m 3 Linear low density polyethylene is sometimes abbreviated as PE-LLD or LLDPE.

[0017] The linear low density polyethylene that can be contained in the resin composition (A) is not particularly limited, and examples thereof include the same linear low density polyethylene as that contained in the resin composition (B) described below. In consideration of the adhesion with the resin layer, it is preferable to blend the linear low density polyethylene of the same material as that of the resin layer in the foam layer.

[0018] The resin composition (A) forming the foam layer preferably contains a mixed resin of linear low density polyethylene and branched low density polyethylene as a main component. In this case, the mass ratio of the branched low density polyethylene to the linear low density polyethylene is preferably branched low density polyethylene: linear low density polyethylene=60:40 to 85:15, more preferably 65:35 to 80:20. In this case, the thermoformability and cushioning properties of the multi-layer extruded foam sheet can be more reliably improved. The mass ratio of the branched low density polyethylene to the linear low density polyethylene in the resin composition (A) is expressed as a ratio (mass % ratio) when the total of the branched low density polyethylene and the linear low density polyethylene is 100 mass %.

[0019] (Crystallization temperature (Tcf) of branched low density polyethylene contained in resin composition (A)) The crystallization temperature (Tcf) of the branched low-density polyethylene which is the main component of the resin composition (A) is not particularly limited, but from the viewpoint of further improving the formability and thermoformability of the multi-layer extruded foam sheet, it is preferably from 90°C to 105°C, more preferably from 92°C to 102°C, and even more preferably from 95°C to 100°C.

[0020] (Measurement of crystallization temperature) The crystallization temperature (°C) derived from the branched low density polyethylene, which is the main component of the resin composition (A), is determined based on a DSC curve measured using a heat flux differential scanning calorimeter in accordance with JIS K7121:2012. A sheet piece made of the resin composition (A) can be used as a test piece for determining the DSC curve. The measurement can be performed as follows. First, a test piece is heated from 23°C to 200°C at a heating rate of 10°C / min, and kept at a temperature of 200°C for 10 minutes, and then a heat flux DSC (i.e., differential scanning calorimetry) is performed to cool the test piece to 30°C at a cooling rate of 10°C / min, and a DSC curve during the cooling process is obtained. The DSC curve can be obtained as a graph with the horizontal axis being temperature (°C) and the vertical axis being heat flow (W / g). In addition, since the measurement of the DSC curve is performed for the resin composition (A), when the resin constituting the resin composition (A) is a mixed resin in which a plurality of types of resins are mixed, a sheet piece containing the mixed resin is used as a test piece to determine the DSC curve. When the resin composition (A) contains various additives described below and these additives remain in the foam layer, a sheet piece containing these various additives is used as a test piece to determine the DSC curve. Then, based on the obtained DSC curve in the cooling process, the crystallization temperature is specified. Specifically, the apex temperature of the exothermic peak corresponding to the crystallization of the branched low-density polyethylene in the DSC curve is the crystallization temperature. When a plurality of exothermic peaks corresponding to the crystallization of the resin appear in the DSC curve, the temperature corresponding to the exothermic peak with the largest area is the crystallization temperature of the branched low-density polyethylene, which is the main component of the resin composition (A).

[0021] (Example of DSC curve for resin composition (A)) When the resin composition (A) is subjected to differential scanning calorimetry, a DSC curve corresponding to the composition of the resin contained in the resin composition (A) is obtained. FIG. 1A is a diagram showing an example of a DSC curve of a resin constituting the resin composition (A). For example, when the resin composition (A) is composed of a mixed resin of a branched low-density polyethylene and a linear low-density polyethylene, a peak CP1 derived from the crystallization of the branched low-density polyethylene appears in the DSC curve as shown in FIG. 1A, and further, a peak CP2 derived from the crystallization of the linear low-density polyethylene appears on the higher temperature side than the apex of the peak CP1. Therefore, based on the DSC curve, the apex temperature of the peak CP1 on the lower temperature side can be determined as the crystallization temperature Tcf derived from the branched low-density polyethylene, as shown by the arrow in FIG. 1A. In addition, in FIG. 1A, the dashed line represented by the symbol BL1 is a straight line connecting the point α1 at 40° C. on the DSC curve and the point β1 on the DSC curve corresponding to the temperature at which the exothermic peak CP2 on the higher temperature side returns to the baseline on the higher temperature side along the DSC curve. The dashed line extending in the vertical direction, denoted by DL1, is a straight line perpendicular to the horizontal axis of the graph, passing through point γ1 on the DSC curve, which is the bottom of a downwardly convex valley formed between an upwardly convex low-temperature side exothermic peak CP1 and an upwardly convex high-temperature side exothermic peak CP2. The area of ​​the low-temperature side exothermic peak CP1 is the area of ​​the portion surrounded by the DSC curve corresponding to peak CP1, dashed lines DL1 and BL1. The area of ​​the high-temperature side exothermic peak CP2 is the area of ​​the portion surrounded by the DSC curve corresponding to peak CP2, dashed lines DL1 and BL1. In FIG. 1A, the arrows on both the horizontal and vertical axes indicate increasing values.

[0022] The melting point (° C.) of the resin composition (A) is preferably 95° C. or more and 120° C. or less, more preferably 100° C. or more and 115° C. or less, from the viewpoints of extrusion foamability, cushioning properties, etc.

[0023] (Melt point measurement) The melting point (°C) of the resin composition (A) is determined based on a DSC curve measured using a heat flux differential scanning calorimeter in accordance with JIS K7121:2012. A sheet piece made of the resin composition (A) can be used as a test piece for determining the DSC curve. First, in accordance with "(2) When measuring the melting temperature after a certain heat treatment", the heating rate and cooling rate are set to 10°C / min to condition the test piece. Then, a heat flux DSC (i.e., differential scanning calorimetry) is performed by heating from 30°C to 200°C at a heating rate of 10°C / min to obtain a DSC curve. The apex temperature of the endothermic peak corresponding to the melting of the resin in the DSC curve is taken as the melting point (°C) of the resin composition (A). In addition, when a plurality of peaks corresponding to the melting of the resin appear in the DSC curve, the apex temperature of the peak with the greatest peak intensity among the peaks corresponding to the melting is taken as the melting point (°C) of the resin composition (A). Specifically, based on the baseline on the high temperature side of the DSC curve, the melting peak with the greatest peak height is determined as the peak with the greatest peak intensity, and the apex temperature of this peak is taken as the melting point.

[0024] (Other polymers) The resin composition (A) may contain other polymers other than polyethylene-based resins. Examples of other polymers include thermoplastic resins such as polystyrene-based resins and thermoplastic elastomers. The content of these other polymers is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, based on 100% by mass of the resin composition (A). It is particularly preferable that the content of these other polymers is 0, that is, the resin composition (A) contains only polyethylene-based resins as polymers.

[0025] (Shrinkage prevention agent) The resin composition (A) may contain a shrinkage inhibitor. The shrinkage inhibitor is one or more compounds selected from the group consisting of fatty acid esters, fatty amines, and fatty acid amides. Among them, preferred examples of shrinkage inhibitors include fatty acid esters such as monostearate glyceride.

[0026] The fatty acid ester is preferably an ester of a fatty acid having 8 to 30 carbon atoms and a polyhydric alcohol having 3 to 7 hydroxyl groups. Examples of fatty acids having 8 or more carbon atoms include lauric acid, oleic acid, stearic acid, behenic acid, lignoceric acid, cerotic acid, heptacoic acid, montanic acid, melissic acid, and lacteric acid. Examples of polyhydric alcohols having 3 to 7 hydroxyl groups include glycerin, diglycerin, triglycerin, erythritol arabic acid, xylymaat, mannitol, sorbitol, and sorbitan. Among these ester compounds, partial esters, particularly monoesters, are preferred over complete esters from the viewpoint of obtaining a more significant shrinkage prevention effect, and monostearate glyceride, behenate monoglyceride, or a mixture of monostearate glyceride and behenate monoglyceride are more preferred.

[0027] Examples of the aliphatic amine include dodecylamine, tetradecylamine, hexadecylamine, octadecylamine, eicosylamine, docosylamine, N-methyloctadecylamine, N-ethyloctadecylamine, hexadecylpropylenediamine, and octadecylpropylenediamine.

[0028] Examples of fatty acid amides include lauric acid amide, myristic acid amide, palmitic acid amide, stearic acid amide, N-methylstearic acid amide, N-ethylstearic acid amide, N,N-dimethylstearic acid amide, N,N-diethylstearic acid amide, dilauric acid amide, distearic acid amide, trilauric acid amide, and tristearic acid amide.

[0029] The content of the shrinkage inhibitor that may be contained in the resin composition (A) can be 0.7 parts by mass or more and 3 parts by mass or less per 100 parts by mass of the polyethylene resin component that constitutes the resin composition (A), from the viewpoint of enabling the effect of the shrinkage inhibitor to be exerted with as small an amount as possible, and the upper limit of the shrinkage inhibitor can be 2 parts by mass.

[0030] When the resin composition (A) contains a shrinkage-preventing agent, the foam layer contains the shrinkage-preventing agent, and therefore shrinkage of the foam layer is suppressed. However, when emphasis is placed on the viewpoint of efficiently suppressing drawdown during thermoforming of the multi-layer extruded foam sheet, it is preferable that the foam layer does not substantially contain a shrinkage-preventing agent, that is, it is preferable that the resin composition (A) does not substantially contain a shrinkage-preventing agent.

[0031] When the foam layer is substantially free of a shrinkage inhibitor, it is preferred that a resin layer be formed on both sides of the foam layer in order to reduce the rate of vaporization of the physical foaming agent from the foam layer and thereby suppress shrinkage of the multi-layer extruded foam sheet.

[0032] The expression "substantially free of shrinkage inhibitor" in the foam layer indicates that "the amount of shrinkage inhibitor in the foam layer is preferably in a numerical range of 0.3 parts by mass or less (including 0) relative to 100 parts by mass of the polyethylene resin constituting the foam layer", but this numerical range is more preferably 0.1 parts by mass or less (including 0), and it is even more preferable that it is 0, i.e., no shrinkage inhibitor is blended. The same applies to the resin composition (A). The expression "substantially free of shrinkage inhibitor" in the resin composition (A) indicates that "the amount of shrinkage inhibitor added in the resin composition (A) is preferably in a numerical range of 0.3 parts by mass or less (including 0) relative to 100 parts by mass of the polyethylene resin contained in the resin composition (A)", but this numerical range is more preferably 0.1 parts by mass or less (including 0), and it is even more preferable that it is 0, i.e., no shrinkage inhibitor is blended.

[0033] (Additives) The resin composition (A) may contain various additives in addition to the above-mentioned shrinkage inhibitor. Examples of the various additives include function-imparting agents such as cell regulators, antioxidants, heat stabilizers, antistatic agents, conductivity-imparting agents, weather resistance agents, ultraviolet absorbers, and flame retardants, as well as inorganic fillers. The amount of these additives added can be adjusted depending on the purpose, and can be, for example, 0.1 parts by mass or more and 3 parts by mass or less relative to 100 parts by mass of the polyethylene resin constituting the resin composition (A).

[0034] (Resin layer) The multi-layer extruded foam sheet has a resin layer on at least one side of the foam layer. The resin layer is composed of a polyethylene-based resin composition (resin composition for forming a resin layer) containing a polyethylene-based resin as a main component. In this specification, this polyethylene-based resin composition is a resin composition for forming a resin layer, which is a resin composition for forming a resin layer. The polyethylene-based resin composition that becomes the resin composition for forming a resin layer is sometimes referred to as resin composition (B).

[0035] (Crystallization temperature of polyethylene resin composition) The crystallization temperature (Tcr) of the polyethylene resin composition which is the resin composition (B) is 108°C or less. If the crystallization temperature (Tcr) of the polyethylene resin composition which is the resin layer composition (B) is too high, the thermoformability of the multi-layer extrusion foam sheet may be insufficient. In addition, the rigidity of the molded product obtained by thermoforming may be reduced. This is considered to be because the resin layer is likely to solidify early during the production of the multi-layer extrusion foam sheet, and distortion due to the orientation of crystals is likely to occur in the multi-layer extrusion foam sheet. Furthermore, when the crystallization temperature (Tcr) is within the above range, the range of extrusion foaming temperature when producing a multi-layer extrusion foam sheet having excellent thermoformability can be expanded, and the manufacturing stability is improved. From the viewpoint of further improving the thermoformability of the multi-layer extrusion foam sheet and further increasing the rigidity of the molded product obtained, the crystallization temperature (Tcr) of the resin composition (B) is preferably 107°C or less, more preferably 106°C or less. The lower limit of the crystallization temperature (Tcr) of the resin composition (B) is not particularly limited, but is preferably 100°C or more, more preferably 102°C or more.

[0036] The crystallization temperature of the resin composition (B) is measured by the same method as that for measuring the crystallization temperature of the branched low-density polyethylene constituting the resin composition (A). Specifically, it is determined based on a DSC curve measured using a heat flux differential scanning calorimeter in accordance with JIS K7121:2012. However, when a plurality of peaks corresponding to the crystallization temperature appear on the DSC curve, the apex temperature of the exothermic peak appearing on the highest temperature side is taken as the crystallization temperature Tcr of the resin composition (B).

[0037] (Example of DSC curve of resin composition (B)) When the above-mentioned differential scanning calorimetry is performed on the polyethylene resin composition, which is the resin composition (B), a DSC curve corresponding to the constitution of the resin contained in the resin composition (B) is obtained. FIG. 1B is a diagram showing an example of a DSC curve of a resin constituting the resin composition (B). For example, when the resin composition (B) is composed of a mixed resin of a linear low-density polyethylene and a branched low-density polyethylene, a peak CPR1 derived from the crystallization of the branched low-density polyethylene appears on the DSC curve as shown in FIG. 1B, and further, a peak CPR2 derived from the crystallization of the linear low-density polyethylene appears on the higher temperature side than the apex of the peak CPR1. Therefore, based on the DSC curve, the apex temperature of the peak CPR2 on the higher temperature side can be determined as the crystallization temperature Tcr of the polyethylene resin composition, as shown by the arrow in FIG. 1B. In addition, in FIG. 1B, the dashed line represented by the symbol BL2 is a straight line connecting the point α2 at 40° C. on the DSC curve and the point β2 on the DSC curve corresponding to the temperature at which the exothermic peak CPR2 on the higher temperature side returns to the baseline on the higher temperature side along the DSC curve. In Fig. 1B, the dashed line extending in the vertical direction, designated by the symbol DL2, is a straight line that passes through point γ2 on the DSC curve, which is the bottom of a downward convex valley formed between an upward convex low-temperature peak CP1 and an upward convex high-temperature exothermic peak CP2, and is perpendicular to the horizontal axis of the graph. In Fig. 1B, the arrows on both the horizontal and vertical axes indicate directions in which values ​​increase.

[0038] The melting point (° C.) of the resin composition (B) is preferably from 95° C. to 120° C., more preferably from 100° C. to 115° C., from the viewpoint of heat resistance and the like.

[0039] (Measurement of Melting Point of Resin Composition (B)) The melting point (°C) of the resin composition (B) is determined based on a DSC curve measured using a heat flux differential scanning calorimeter in accordance with JIS K7121:2012. A sheet piece made of the resin composition (B) can be used as a test piece for determining the DSC curve. First, according to "(2) When performing a certain heat treatment and then measuring the melting temperature", the heating rate and cooling rate are set to 10°C / min to condition the test piece. Then, the heating rate is set to 10°C / min to perform heat flux DSC (i.e., differential scanning calorimetry) to obtain a DSC curve. The apex temperature of the endothermic peak corresponding to the melting of the resin in the DSC curve is taken as the melting point (°C) of the resin composition (B). In addition, when a plurality of peaks corresponding to the melting of the resin appear in the DSC curve, the apex temperature of the peak with the greatest peak intensity among the peaks corresponding to the melting is taken as the melting point (°C) of the resin constituting the resin composition (B). Specifically, based on the baseline on the high temperature side of the DSC curve, the melting peak with the greatest peak height is determined as the peak with the greatest peak intensity, and the apex temperature of this peak is taken as the melting point.

[0040] (Relationship between Tcr and Tcf) The difference [Tcr-Tcf] between the crystallization temperature (Tcf) of the branched low density polyethylene constituting the resin composition (A) and the crystallization temperature (Tcr) of the resin composition (B) is preferably 0 to 10°C. When [Tcr-Tcf] is 10°C or less, a molding range in which thermoforming can be performed well can be secured more widely even when the thickness of the multi-layer extrusion foam sheet is thin or the basis weight is small. Furthermore, when [Tcr-Tcf] is 10°C or less, the rigidity of the multi-layer extrusion foam sheet can be improved while maintaining the thermoformability. This is considered to be because the thickness of each part of the molded product obtained by thermoforming is more uniform. Furthermore, when [Tcr-Tcf] is within the above range, the extrusion foaming temperature range when producing a multi-layer extrusion foam sheet having excellent thermoformability can be expanded, and production stability is improved. From the viewpoint of further improving the thermoformability of the multi-layer extrusion foam sheet and further increasing the rigidity of the molded product obtained, the difference [Tcr-Tcf] of the crystallization temperature is preferably 9°C or less. The lower limit of the crystallization temperature difference [Tcr-Tcf] is not particularly limited as long as it is 0 or more, but it is preferably 3°C or more, and more preferably 5°C or more.

[0041] (Tensile product of polyethylene resin composition constituting resin layer) The product of the tensile strength (MPa) and the tensile elongation (%) of the resin composition (B) which is a polyethylene resin composition constituting the resin layer at 110°C (sometimes referred to as the tensile product) is 1300 (MPa·%) or more. If the tensile product of the resin composition (B) at 110°C is too small, the moldability may decrease, especially when the thickness of the multi-layer extruded foam sheet is thin or the basis weight is small. This is considered to be because the multi-layer extruded foam sheet is excessively stretched during thermoforming, and the thickness of the molded product obtained is likely to decrease. From the viewpoint of further improving the moldability even when the thickness of the multi-layer extruded foam sheet is thin or the basis weight is small, the tensile product, which is the product of the tensile strength (MPa) and the tensile elongation (%) of the resin composition (B) is preferably 1600 (MPa·%) or more. The upper limit of the tensile product of the resin composition (B) at 110°C is not particularly limited, but is generally 3000 (MPa·%).

[0042] (Tensile elongation and tensile strength) The tensile strength (MPa) of the resin composition (B) is measured based on JIS K7161-1:2014. In addition to the recommended temperature condition of 23°C, 110°C is adopted as the temperature condition of the test atmosphere. Taking into consideration the extrusion foaming temperature and the temperature during thermoforming when producing a multi-layer extruded foam sheet, 110°C is adopted as the temperature condition of the test atmosphere. The tensile strength is the maximum stress observed during the test, and is usually the maximum stress at break.

[0043] The tensile elongation (%) of the resin composition (B) is measured based on JIS K7161-1:2014, similarly to the tensile strength. As for the temperature conditions of the test atmosphere, 23°C and 110°C are adopted, similarly to the tensile strength. The tensile elongation (%) is specified as the elongation rate at the break of the resin layer when measuring the tensile strength. The tensile elongation is a value calculated based on the gauge length (e.g., 40 mm) of a dumbbell-shaped No. 1 specimen.

[0044] As described later, when the resin composition (B) contains an additive such as a shrinkage inhibitor, the resin composition (B) used to prepare the test specimen for the measurement of the tensile elongation and tensile strength contains the additive. In addition, the test specimen is conditioned for the measurement of the tensile elongation and tensile strength, and in this conditioning, the test specimen is left to stand in an atmosphere of 23°C and 50% humidity for 16 hours or more.

[0045] (Temperature Dependence of Tensile Elongation of Resin Composition (B)) The ratio (TE2 / TE1) of the tensile elongation (TE2) (%) of the resin composition (B) at 110°C to the tensile elongation (TE1) (%) of the resin composition (B) at 23°C is preferably 0.3 or more. When TE2 / TE1 is 0.3 or more, the tensile elongation property of the resin composition (B) at room temperature (23°C) can be maintained to a certain degree even at high temperature (110°C). Resin compositions (B) that maintain a high tensile elongation (%) even at high temperatures such as 110°C are more advantageous in terms of further exerting the effects of improving thermoformability and rigidity than those that have a low tensile elongation (%) at high temperatures. The upper limit of the ratio (TE2 / TE1) is 1.

[0046] (Composition of Resin Composition (B)) The polyethylene-based resin constituting the resin composition (B) forming the resin layer is not particularly limited as long as the resin composition (B) satisfies the above-mentioned conditions of crystallization temperature, tensile product, etc., but from the viewpoint of easily satisfying these conditions, it is preferable that the resin composition (B) contains linear low-density polyethylene. When the resin composition (B) contains linear low-density polyethylene, this may include the case where the resin composition (B) contains only linear low-density polyethylene as the polyethylene-based resin.

[0047] (Linear low density polyethylene) The linear low-density polyethylene (sometimes abbreviated as PE-LLD or LLDPE) that may be contained in the resin composition (B) is a copolymer of ethylene and an α-olefin, has a linear polyethylene main chain and short-chain branches of an α-olefin having about 4 to 8 carbon atoms, and has a density of 910 kg / m 3 More than 930kg / m 3The linear low density polyethylene is less than 100%. When the resin composition (B) contains the linear low density polyethylene, the rigidity of the multi-layer extruded foam sheet can be improved, and the rigidity of the molded article obtained by thermoforming can also be improved. From the same viewpoint, the melting point of the linear low density polyethylene that may be contained in the resin composition (B) is preferably 110°C or more and 128°C or less, more preferably 115°C or more and 125°C or less. The α-olefin constituting the copolymer that is the linear low density polyethylene may be referred to as a comonomer.

[0048] It is also preferred that the resin composition (B) has a tensile product of 1600 (MPa·%) or more and is substantially free of a shrinkage inhibitor. In this case, even if the thickness of the multi-layer extruded foam sheet is thin or the basis weight is small, the feasibility of more difficult molding such as deep drawing can be improved. This is believed to be because the resin composition (B) forming the resin layer has a tensile product of a certain value or more and is substantially free of a shrinkage inhibitor, which further improves the physical properties of the surface layer of the multi-layer extruded foam sheet and improves the uniformity of elongation of the multi-layer extruded foam sheet during thermoforming. The tensile product being equal to or greater than the above-mentioned value and resin composition (B) being substantially free of a shrinkage inhibitor specifically means that the tensile product of resin composition (B) is 1600 (MPa·%) or greater, and the amount of shrinkage inhibitor in resin composition (B) is preferably in the range of 0.3 parts by mass or less (including 0) per 100 parts by mass of the polyethylene resin constituting resin composition (B), more preferably 0.1 parts by mass or less (including 0). And it is even more preferable that this range is 0, that is, that resin composition (B) does not contain a shrinkage inhibitor.

[0049] Furthermore, as described above, the tensile product of resin composition (B) can be made 1600 (MPa %) without substantially including a shrinkage inhibitor, and even when the multi-layer extruded foam sheet is thin or has a small basis weight, from the viewpoint of enhancing the feasibility of more difficult molding, it is preferable that resin composition (B) contains a copolymer of ethylene and an α-olefin having 8 carbon atoms as the linear low-density polyethylene. In this case, even when no shrinkage inhibitor is blended in the resin layer, shrinkage of the multi-layer extruded foam sheet is likely to be mitigated.

[0050] (Other polyethylene resins) The resin composition (B) may contain other polyethylene-based resins different from the linear low-density polyethylene described above. Examples of other polyethylene-based resins include branched low-density polyethylene and high-density polyethylene. The branched low-density polyethylene is defined similarly to the branched low-density polyethylene contained in the resin composition (A) forming the foamed layer. However, from the viewpoint of setting the crystallization temperature (Tcr) of the resin composition (B) within the above-mentioned predetermined range, the content of the high-density polyethylene is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 0% by mass, that is, the resin composition (B) does not contain high-density polyethylene, based on 100% by mass of the resin composition (B).

[0051] In the resin composition (B), from the viewpoint of easily adjusting the crystallization temperature (Tcr) and the tensile product at 110°C within the above-mentioned ranges, it is preferable that the resin composition (B) mainly comprises a mixed resin of linear low-density polyethylene and branched low-density polyethylene. From the viewpoint of improving the thermoformability of the multi-layer extrusion foam sheet and of obtaining a molded product having superior rigidity by thermoforming the multi-layer extrusion foam sheet, the mass ratio of the linear low-density polyethylene to the branched low-density polyethylene is preferably linear low-density polyethylene:branched low-density polyethylene=90:10 to 30:70, more preferably 80:20 to 40:60, and even more preferably 75:25 to 50:50. Note that, with regard to the mass ratio (mass%) of the linear low-density polyethylene to the branched low-density polyethylene, the total of the linear low-density polyethylene and the branched low-density polyethylene is taken as 100 parts by mass.

[0052] The resin composition (B) may contain a shrinkage inhibitor.

[0053] (Shrinkage prevention agent) The shrinkage inhibitor that may be contained in the resin composition (B) is the same as the various compounds shown as examples of the shrinkage inhibitor that may be contained in the resin composition (A), that is, one or more compounds selected from the group consisting of fatty acid esters, fatty amines, and fatty acid amides. Specific examples of fatty acid esters, fatty amines, and fatty acid amides are the same as the examples shown in the explanation of the shrinkage inhibitor that may be contained in the foam layer, so detailed explanations are omitted.

[0054] From the viewpoint of ensuring that the effect of the shrinkage prevention agent can be exerted with as small an amount as possible, the content of the shrinkage prevention agent that may be contained in the resin composition (B) is preferably 0.7 parts by mass or more and 3 parts by mass or less per 100 parts by mass of the polyethylene resin that constitutes the resin composition (B), and the upper limit of the shrinkage prevention agent is more preferably 2 parts by mass.

[0055] When the resin composition (B) contains a shrinkage inhibitor, the resin composition (A) may contain a shrinkage inhibitor, but from the viewpoint of further improving thermoformability, it is preferable that the foam layer does not substantially contain a shrinkage inhibitor, and therefore it is preferable that the resin composition (A) does not substantially contain a shrinkage inhibitor. Therefore, the multi-layer extrusion foam sheet according to the present invention may be configured such that the resin composition (B) contains a shrinkage inhibitor, the blending amount of the shrinkage inhibitor in the resin composition (B) is 0.7 parts by mass or more and 3 parts by mass or less with respect to 100 parts by mass of the polyethylene-based resin contained in the resin composition (B), and the resin composition (A) does not substantially contain a shrinkage inhibitor. If the resin layer contains a shrinkage inhibitor, it is possible to exert the shrinkage prevention effect of the multi-layer extrusion foam sheet. In addition, by not blending a shrinkage inhibitor in the foam layer (constituting the foam layer so that it does not substantially contain a shrinkage inhibitor), the heat resistance of the multi-layer extrusion foam sheet can be increased and thermoformability can be further improved.

[0056] When the resin layer is formed on both sides of the foam layer, only one of the resin layers may contain a shrinkage inhibitor, or both of the resin layers formed on both sides of the foam layer may contain a shrinkage inhibitor. From the viewpoint of more efficiently suppressing the volatilization of the foaming agent from the foam layer, when the resin layer is formed on both sides of the foam layer, it is preferable that both of the resin layers formed on both sides of the foam layer contain a shrinkage inhibitor.

[0057] (Additives) The resin composition (B) may contain various additives in addition to the above-mentioned shrinkage inhibitor. Examples of the various additives include functional agents such as antioxidants, heat stabilizers, antistatic agents, conductivity-imparting agents, weather resistance agents, ultraviolet absorbers, and flame retardants, as well as inorganic fillers.

[0058] (Thickness of multi-layer extruded foam sheet) The thickness (total thickness) (mm) of the multi-layer extruded foam sheet is not particularly limited, but is preferably in the range of 1 mm to 7 mm. When the thickness of the multi-layer extruded foam sheet is within this range, it is easy to produce a molded article such as a cushioning material by thermoforming. Furthermore, according to the present invention, even if the thickness of the multi-layer extruded foam sheet is relatively thin, 1 mm or more and 3.5 mm or less, the thermoformability of the multi-layer extruded foam sheet can be improved, and a molded article with excellent rigidity can be obtained by thermoforming the multi-layer extruded foam sheet. The total thickness of the multi-layer extruded foam sheet is the total thickness of the foam layer and the resin layer.

[0059] The total thickness of the multi-layer extruded foam sheet can be measured, for example, as follows. The multi-layer extruded foam sheet is cut in a plane perpendicular to the extrusion direction. Ten measurement positions are set on this cut surface so as to divide the length of the width direction of the cut surface (i.e., the direction perpendicular to both the extrusion direction and the thickness direction) into 11 equal parts. The thickness at each measurement position is measured by observing these measurement positions using a microscope, for example. The arithmetic average value of these thicknesses is then determined as the total thickness of the multi-layer foam sheet.

[0060] (Basis weight of multi-layer extruded foam sheet) The basis weight (total basis weight) of the multi-layer extruded foam sheet is not particularly limited, but is preferably 30 g / m 2 from 300 g / m 2 In view of the possibility of thermoforming the multi-layer extruded foam sheet according to various applications, it is preferable that the basis weight of the multi-layer extruded foam sheet is in the range of 150 g / m. 2 Even if the multi-layer extruded foam sheet is relatively light as described below, the thermoformability of the multi-layer extruded foam sheet can be improved, and a molded product having excellent rigidity can be obtained by thermoforming the multi-layer extruded foam sheet. The total basis weight of the multi-layer extruded foam sheet is the combined basis weight of the foam layer and the resin layer.

[0061] The total basis weight of the multi-layer extruded foam sheet can be measured, for example, as follows: A sample is cut out from the multi-layer foam sheet, the weight of the sample is measured, and the measured value is multiplied by 1 m2 This is converted into the weight (g) of the multi-layer extruded foam sheet per unit area, and the resulting weight is calculated as the basis weight (g / m 2 Specifically, a test piece measuring 250 mm long x 250 mm wide is cut out from the multilayer foamed sheet obtained, the weight (g) of the test piece is measured, and the weight is multiplied by 16 to obtain the test piece of 1 m 2 Value converted to weight per unit (g / m 2 This value is defined as the total basis weight of the multi-layer extruded foam sheet.

[0062] In the multi-layer extruded foam sheet, the basis weight of the resin layer and the basis weight of the foam layer can also be specified. The basis weight of the resin layer can be specified, for example, by the following first method or second method.

[0063] (First Method) In the first method, the basis weight of the resin layer can be calculated from the average thickness of the resin layer and the density of the resin constituting the resin layer. Specifically, ten measurement points are set at approximately equal intervals in the width direction over the entire width of the resin layer, and the arithmetic mean value of the thicknesses of the resin layer at the measurement points is taken as the average thickness of the resin layer. The value obtained by multiplying the average thickness of the resin layer by the density of the resin constituting the resin layer is then converted into a unit (g / m 2 ) to calculate the basis weight of the resin layer. Note that the density (g / cm 3 ) can be obtained as the sum of values ​​calculated by multiplying the density of each resin constituting the resin layer by the mass content ratio of each resin.

[0064] (Second Method) In the second method, when the multi-layer extruded foam sheet is a sheet produced by coextrusion, the basis weight of the resin layer is calculated based on the discharge amount from a coextrusion die.

[0065] Specifically, when the extrusion rate per side of the resin layer-forming molten material obtained by melting the resin composition (B) is X [kg / hour], the width of the resulting multi-layer extruded foam sheet is W [m], and the length of the multi-layer extruded foam sheet extruded per unit time is L [m / hour], the basis weight of the resin layer per side [g / m2 ] is the basis weight (kg / m2) calculated by the formula [X / (L×W)] 2 ) to g / m 2 When resin layers are formed on both sides of the multi-layer extruded foam sheet, the basis weight of each resin layer can be calculated based on the amount of the melt for forming the resin layer for forming each resin layer.

[0066] The basis weight of the foam layer [g / m 2 ] can be calculated by applying the same method as the second method described above using the discharge amount of the molten material for forming the foamed layer containing the resin composition (A) and the physical foaming agent. 2 ] is the basis weight [g / m2] of the multi-layer extruded foam sheet 2 ] to the basis weight of the resin layer [g / m 2 ] is determined by subtracting

[0067] The above-mentioned methods for specifying the basis weight are merely examples, and the method for specifying the basis weight is not limited to these methods.

[0068] The basis weight of the resin layer on one side of the multi-layer extruded foam sheet is set to 5 g / m from the viewpoint of weight reduction and ensuring the above-mentioned effects of the resin layer. 2 From 30g / m 2 It is preferable that the range is 7 g / m 2 From 25 g / m 2 More preferably, it is within the range of 10 g / m 2 From 20g / m 2 It is more preferable that the range is within the range.

[0069] (Closed cell ratio of multi-layer extruded foam sheet) The closed cell percentage (%) of the multi-layer extruded foam sheet is not particularly limited, but is preferably 40% or more from the viewpoints of improving the thermoformability of the multi-layer extruded foam sheet and obtaining a molded product having relatively excellent rigidity by thermoforming the multi-layer extruded foam sheet. From the viewpoints of improving the thermoformability and rigidity, the closed cell percentage (%) of the multi-layer extruded foam sheet is preferably 50% or more, more preferably 60% or more.

[0070] (Measurement of closed cell ratio) A test piece having dimensions of 25 mm length x 25 mm width x thickness of the multilayer extruded foam sheet is cut out from the multilayer extruded foam sheet. A plurality of test pieces are stacked so that the total thickness is closest to 20 mm to prepare a test piece for measurement. Next, according to procedure C of ASTM-D2856-70, the true volume Vx of the test piece for measurement is measured using an air comparison specific gravity meter Model 930 of Toshiba Beckman Co., Ltd., and the closed cell ratio (%) is calculated using the following formula (Formula (1)). The above measurement is performed using five test pieces for measurement, and the arithmetic average value is taken as the closed cell ratio of the foam layer. Note that the length and width are specified as the directions (length and width) determined in the direction in which the surface of the multilayer extruded foam sheet spreads.

[0071]

number

[0072] however, Vx: The true volume (cm) of the test piece measured by the above method 3 ) which corresponds to the sum of the volume of the resin constituting the test piece and the total volume of the air bubbles in the closed cell part in the test piece. Va: Apparent volume (cm) of the test specimen calculated from the outer dimensions of the test specimen used in the measurement 3 ), W: total mass of the test specimens used in the measurement (g), and ρ: Density of the resin obtained by defoaming the multi-layer extruded foam sheet (g / cm 3 ), It is.

[0073] (non-crosslinked) The multi-layer extruded foam sheet is preferably non-crosslinked. The term "non-crosslinked" in the multi-layer extruded foam sheet means that both the foam layer and the resin layer are non-crosslinked. Specifically, the term "non-crosslinked" in the multi-layer extruded foam sheet means that the insoluble matter of the multi-layer extruded foam sheet measured by hot xylene extraction is 5% by mass or less. From the viewpoint of further improving the cushioning property of the multi-layer extruded foam sheet, the proportion of the insoluble matter of the multi-layer extruded foam sheet measured by hot xylene extraction is preferably 3% by mass or less, and most preferably 0.

[0074] (Hot xylene extraction method) The xylene insoluble content (mass%) of the multi-layer extruded foam sheet by the hot xylene extraction method is calculated by cutting a test piece of about 1 g (whose exact weight is Wp(g)) from the multi-layer extruded foam sheet, placing it in a 150 mL round-bottom flask, adding 100 mL of xylene, heating with a mantle heater and refluxing for 6 hours, filtering the undissolved residue through a 100 mesh wire screen, drying in a vacuum dryer at 80°C for 8 hours or more, measuring the weight of the dried product obtained at this time, Wm(g), and calculating the formula shown in the following formula (2). It is preferable to filter the residue quickly through a wire screen.

[0075]

number

[0076] (Apparent density) As a multi-layer extruded foam sheet, its apparent density is 20kg / m 3 More than 200kg / m 3 From the viewpoint of the balance between light weight, cushioning properties, and rigidity, the multi-layer extruded foam sheet has an apparent density of 25 kg / m 3 More than 100kg / m 3 It is preferable that the thickness is less than 30 kg / m 3 More than 80kg / m 3 It is more preferable that:

[0077] (How to calculate apparent density) Apparent density (kg / m) of multi-layer extruded foam sheet 3 ) is calculated by dividing the basis weight of the multi-layer extruded foam sheet by the total thickness of the multi-layer extruded foam sheet, and the unit is kg / m 3 The total thickness and basis weight of the multi-layer extruded foam sheet can be determined by the following measurement methods.

[0078] [2. Method for manufacturing multi-layer extruded foam sheet] The multi-layer extruded foam sheet according to the present invention can be produced, for example, by a co-extrusion foaming method. In the co-extrusion foaming method, a melt for forming a foam layer and a melt for forming a resin layer are co-extruded to obtain a multi-layer extruded foam sheet having a polyethylene-based resin foam layer and a resin layer provided on at least one side of the polyethylene-based resin foam layer. Next, the method for producing a multi-layer extruded foam sheet will be described by taking as an example a case where the multi-layer extruded foam sheet has a structure in which resin layers are formed on both sides of the foam layer and is produced by the co-extrusion foaming method.

[0079] (Co-extrusion equipment) As an extrusion device that can be used to produce a multi-layer extruded foam sheet, for example, a co-extrusion device applicable in the technical field of extrusion foaming can be used. Specific examples of the co-extrusion device include a foam layer forming extruder configured to be able to extrude a foam layer forming melt, a resin layer forming extruder configured to be able to extrude a resin layer forming melt, and a co-extrusion die to which the outlet of the foam layer forming extruder and the outlet of the resin layer forming extruder are connected. In such a co-extrusion device, a multi-layer extruded foam sheet can be produced by co-extruding the foam layer forming melt and the resin layer forming melt from the co-extrusion die. An example of the co-extrusion die is an annular die such as a ring die.

[0080] In the case where resin layers are formed on both sides of the foam layer, the co-extrusion device may be provided with a first resin layer forming extruder (sometimes referred to as the first resin layer forming extruder) configured to be capable of extruding a resin layer forming melt for forming a resin layer provided on one side of the foam layer, and a second resin layer forming extruder (sometimes referred to as the second resin layer forming extruder) configured to be capable of extruding a resin layer forming melt for forming a resin layer provided on the other side of the foam layer. In such a co-extrusion device, a melt laminated in three layers, in which the resin layer forming melt from the first resin layer forming extruder and the foam layer forming melt from the second resin layer forming extruder are disposed between each other, is extruded (co-extruded) from the co-extrusion die, thereby producing a multilayer extruded foam sheet. In the present specification, when the first resin layer forming extruder and the second resin layer forming extruder are not particularly distinguished from each other, they are collectively referred to as the resin layer forming extruder.

[0081] (Melted material for forming foam layer) The foam layer forming melt contains a resin composition (A) mainly composed of branched low density polyethylene and a physical foaming agent. The foam layer forming melt can be obtained, for example, by the following method. Branched low density polyethylene is supplied to the foam layer forming extruder, and melt-kneaded. The foam layer forming extruder may be supplied with other resins different from the branched low density polyethylene as required, and may also be supplied with a bubble regulator and other additives different from the bubble regulator as required. The physical foaming agent is supplied under pressure to the melt containing the branched low density polyethylene melted in the foam layer forming extruder, and the melt supplied with the physical foaming agent is further kneaded. This allows the foam layer forming melt to be obtained.

[0082] (Physical foaming agent) Examples of physical foaming agents include organic physical foaming agents and inorganic physical foaming agents. Examples of organic physical foaming agents include aliphatic hydrocarbons such as propane, normal butane, isobutane, normal pentane, isopentane, normal hexane, and isohexane, alicyclic hydrocarbons such as cyclopentane and cyclohexane, chlorinated hydrocarbons such as methyl chloride and ethyl chloride, and fluorinated hydrocarbons such as 1,1,1,2-tetrafluoroethane and 1,1-difluoroethane. Examples of inorganic physical foaming agents include inorganic substances such as nitrogen, carbon dioxide, air, and water. The type of physical foaming agent contained in the foam layer forming melt may be one type or two or more types (for example, a combination of normal butane and isobutane). From the viewpoints of compatibility with the branched polyethylene and foamability, the foam layer-forming melt preferably contains an organic physical foaming agent as a physical foaming agent, and more preferably contains an organic physical foaming agent containing normal butane, isobutane or a mixture thereof as a main component.

[0083] The amount of the physical foaming agent in the foam layer-forming melt may be determined depending on various conditions such as the type of physical foaming agent and the apparent density of the foam layer to be produced. In the case where a mixed butane consisting of 30 mass% isobutane and 70 mass% normal butane is used as the physical foaming agent, for example, the amount of the physical foaming agent may be set to a value within a range of about 3 parts by mass to 30 parts by mass, preferably a value within a range of 4 parts by mass to 20 parts by mass, and more preferably a value within a range of 10 parts by mass to 20 parts by mass, relative to 100 parts by mass of the polyethylene resin contained in the resin composition (A).

[0084] As described above, it is preferable that a bubble regulator is added to the molten material for forming the foam layer. As the bubble regulator, an inorganic bubble regulator or an organic bubble regulator can be used. As the inorganic bubble regulator, there are metal borate salts such as zinc borate, magnesium borate, and borax, sodium chloride, aluminum hydroxide, talc, zeolite, silica, calcium carbonate, and sodium bicarbonate. As the organic bubble regulator, there are sodium 2,2-methylenebis(4,6-tert-butylphenyl)phosphate, sodium benzoate, aluminum benzoate, and sodium stearate. Furthermore, a mixture of citric acid and sodium bicarbonate, a mixture of an alkali citrate salt and sodium bicarbonate, and the like can also be used as the bubble regulator. The type of the bubble regulator added to the molten material for forming the foam layer may be one type, or a combination of two or more types. The amount of the bubble control agent in the foam layer-forming melt may be appropriately determined depending on the type of physical foaming agent, the various conditions of the foam layer, and the like.

[0085] (Melted material for forming resin layer) The resin layer forming melt contains a polyethylene resin composition as the resin composition (B). The polyethylene resin composition as the resin composition (B) satisfies various conditions such as the tensile product and the crystallization temperature as explained in [1. Polyethylene resin multi-layer extrusion foam sheet for thermoforming] above. That is, the crystallization temperature Tcr of the resin composition (B) is 108°C or less, and the product of the tensile strength (MPa) and the tensile elongation (%) of the resin composition (B) at 110°C is 1300 (MPa·%) or more. In addition, the resin composition (B) preferably contains linear low-density polyethylene, and may further contain branched low-density polyethylene in addition to the linear low-density polyethylene. The resin layer forming melt can be obtained, for example, by the following method. A resin (for example, linear low-density polyethylene) constituting the resin composition (B) is supplied to the resin layer forming extruder and melt-kneaded. A shrinkage inhibitor and other additives different from the shrinkage inhibitor may be supplied to the resin layer forming extruder as necessary. This allows the foam layer forming melt to be obtained.

[0086] The composition of the melt for forming a resin layer formed in the first extruder for forming a resin layer may be the same as or different from the composition of the melt for forming a resin layer formed in the second extruder for forming a resin layer. The various conditions such as the material and composition of the polyethylene-based resin composition supplied to the first extruder for forming a resin layer may be the same as or different from the various conditions such as the material and composition of the polyethylene-based resin composition supplied to the second extruder for forming a resin layer.

[0087] (Co-extrusion) The above-mentioned co-extrusion of the foam layer forming melt and the resin layer forming melt can be carried out, for example, as follows. In the co-extrusion device, the foam layer forming melt is introduced from the foam layer forming extruder to the co-extrusion die. Also, the resin layer forming melt is introduced from the resin layer forming extruder (the first extruder for forming the resin layer and the second extruder for forming the resin layer) to the co-extrusion die and extruded to the outside from the extrusion port of the co-extrusion die. When the co-extrusion die is a circular die, for example, the resin layer forming melt from the resin layer forming first extruder, the foam layer forming melt, and the resin layer forming melt from the resin layer forming second extruder are laminated in three layers in order from the inside, and the laminated melt is extruded in a cylindrical shape from the co-extrusion die. When the laminated melt is extruded from the extrusion port into the atmosphere, the foam layer forming melt expands while foaming, forming a foam layer. Accordingly, a cylindrical laminated foam is formed in which resin layers are laminated on both sides of the foam layer. The cylindrical laminated foam is expanded from the inside with compressed air or the like, and the inside of the cylindrical laminated foam is drawn along a mandrel or other expanding device and cooled while being drawn by a roller or the like, thereby solidifying the foam layer and the resin layer. This largely fixes the cell structure formed in the foam layer. Then, the cylindrical laminated foam is cut open on the expanding device. In this way, a multi-layer extruded foam sheet having a foam layer and a resin layer provided thereon is obtained. The method using a co-extrusion annular die is preferred because it can suppress the occurrence of a wavy pattern called corrugation and can easily produce a wide multi-layer extruded foam sheet having a width of 1000 mm or more.

[0088] In the above description, the laminated melt consisting of the melt for forming the resin layer from the first extruder for forming the resin layer, the melt for forming the foam layer, and the melt for forming the resin layer from the second extruder for forming the resin layer laminated in three layers was discharged from the co-extrusion die, but the laminated melt may be extruded from the co-extrusion die in a state in which the melt for forming the resin layer and the melt for forming the foam layer are laminated in two layers. In this case, the melt for forming the resin layer and the melt for forming the foam layer are laminated so that the cylindrical laminated foam is in a state in which, for example, the melt for forming the resin layer is arranged on the outside and the melt for forming the foam layer is arranged on the inside. The two-layer cylindrical laminated foam extruded from the co-extrusion die is cooled along the widening device as described above, and the cylindrical laminated foam is cut open on the widening device. In this case, a sheet having a resin layer formed on one side of the foam is obtained as a multilayer extruded foam sheet. In addition, the two-layer cylindrical laminated foam extruded from the co-extrusion die may be crushed to form a sheet, thereby obtaining a multi-layer extruded foam sheet in which resin layers are formed on both sides of the foam.

[0089] In the above description of the method for producing a multilayer extruded foam sheet, the co-extrusion die is an annular die, but the co-extrusion die may be a flat die. In this case, a three-layer laminated melt is extruded in a sheet shape from the extrusion port of the flat die. When the three-layer laminated melt is extruded from the extrusion port into the atmosphere, the melt for forming the foam layer expands while foaming. This forms a sheet-like laminated foam in which the foam layer and the resin layer are laminated. Then, the sheet-like laminated foam extruded from the extrusion port is drawn along the widening device and cooled to solidify the foam layer and the resin layer. This fixes the cell structure of the foam layer and stabilizes the dimensions. This allows a multilayer extruded foam sheet to be obtained.

[0090] As described above, in the manufacturing method for producing the multi-layer extrusion foam sheet according to the present invention, a foam layer forming melt obtained by kneading a resin composition (A) mainly composed of a branched low density polyethylene and a physical foaming agent and a resin layer forming melt obtained by melt kneading a polyethylene-based resin composition as the resin composition (B) are co-extruded to laminate a polyethylene-based resin layer composed of the resin composition (B) as a polyethylene-based resin composition on at least one side of the polyethylene-based resin foam layer mainly composed of a branched low density polyethylene, thereby producing a multi-layer extrusion foam sheet for thermoforming, in which the crystallization temperature Tcr of the resin composition (B) is 108°C or lower, and the product of the tensile strength (MPa) and the tensile elongation (%) at 110°C of the resin composition (B) is 1300 (MPa·%) or higher. In this case, the foaming temperature range (°C) required for forming a good multi-layer extrusion foam sheet can be effectively and widely secured. The good multi-layer extrusion foam sheet referred to here refers to a multi-layer extrusion foam sheet that can secure a moldable time range of a predetermined value or more when thermoforming a molded product from the multi-layer extrusion foam sheet.

[0091] [3. Actions and Effects] An extruded polyethylene resin foam sheet for thermoforming has a problem that the rigidity of the molded article obtained by thermoforming may be insufficient.

[0092] According to the multi-layer extruded polyethylene resin foam sheet for thermoforming of the present invention (the multi-layer extruded foam sheet of the present invention), a resin layer that satisfies specific conditions is provided on at least one side of the foam layer, whereby a molded product having good rigidity can be obtained by thermoforming.

[0093] In addition, when a molded product having a small thickness or a small basis weight is obtained by thermoforming, it is required to use a polyethylene resin extrusion foam sheet for thermoforming having a small thickness or a small basis weight. With conventional polyethylene resin extrusion foam sheets for thermoforming, when a molded product having a small thickness or a small basis weight is obtained, the heating time range (molding range, molding time range) that can realize good thermoforming is likely to be narrow, and there is room for improvement in moldability. If the heating time is out of the appropriate range, the molded product obtained by thermoforming of the polyethylene resin extrusion foam sheet for thermoforming has tears or thickness deviations (sometimes discoloration occurs), and it is not easy to obtain a good molded product. In addition, the rigidity of the obtained molded product is likely to decrease.

[0094] According to the multi-layer extruded foam sheet of the present invention, even when a molded product having a small thickness or basis weight is obtained, a molding range in which thermoforming can be satisfactorily achieved can be secured more widely. In addition, thickness unevenness of the molded product obtained by thermoforming is easily suppressed, and a molded product having good rigidity can be obtained.

[0095] Specifically, the multi-layer extruded foam sheet of the present invention can ensure a wider range of favorable molding even when the sheet has a small thickness of 1 mm or more and 3.5 mm or less, and can provide favorable thermoformability, thereby obtaining a molded product having favorable rigidity by thermoforming. 2 Even with a basis weight as small as or less than this, a wider range of molding that can be satisfactorily realized as described above can be ensured, the thermoformability can be improved, and a molded body with good rigidity can be obtained by thermoforming.

[0096] [4. Application Examples] The multi-layer extruded foam sheet according to the present invention can be used as a raw material sheet for obtaining a molded product by thermoforming. Thermoforming is a production method in which a raw material sheet is heated to a softened state, and then deformed by applying an external force such as vacuum, compressed air, or a press to mold the sheet into a desired shape.

[0097] By using the multilayer extruded foam sheet according to the present invention as a raw material sheet for thermoforming, a thermoformed product with increased rigidity can be efficiently obtained. In addition, the range of heating time for the raw material sheet during thermoforming can be secured, and the moldability (thermoformability) during thermoforming can be improved (a good molded product can be obtained even with relatively loose heating time management).

[0098] The use of the obtained molded article is not particularly limited, and it can be used, for example, as a cushioning material, a packaging member, etc. An example of a cushioning material is a packaging container shaped to prevent food such as fruit from being scratched or dented.

[0099] Next, a more detailed explanation will be given using a specific example. EXAMPLES

[0100] (Resin preparation) As shown in Table 1, various resins identified as LLDPE1 to LLDPE8 in the type column were prepared as linear low density polyethylene. Also, as shown in Table 1, a resin indicated as LDPE in the type column was prepared as branched low density polyethylene.

[0101] Table 1 shows the contents (manufacturer name, product name, etc.), comonomers, and density (g / cm 3 ), MFR (g / 10min), and melting point (℃). Table 1 also shows the details (manufacturing company name, product name, etc.) and density (g / cm 3 ), MFR (g / 10 min), and melting point (°C) are also shown.

[0102] "MFR" in Table 1 is the melt flow rate (g / 10 min) measured at 190°C and a load of 2.16 kg according to the method specified in JIS K7210-1 (2014). The "melting point" in Table 1 is the melting point at the apex temperature of the maximum endothermic peak in the DSC curve measured using a heat flux differential scanning calorimeter in accordance with JIS K7121:2012.

[0103] (Preparation of anti-shrinkage agent) A shrinkage inhibitor master batch was used in which monostearate glyceride was mixed as a shrinkage inhibitor with polyethylene resin (LDPE) at a concentration of 12 mass%. The shrinkage inhibitor master batch is shown as "Shrinkage inhibitor MB" in Tables 2, 3, and 4.

[0104] (Co-extrusion equipment) The co-extrusion device used was equipped with a tandem extruder in which a first extruder and a second extruder were connected, two sub-extruders, and a co-extrusion die to which the outlets of both the tandem extruder and the sub-extruder were connected. The tandem extruder was an extruder for forming a foam layer, and both of the sub-extruders were extruders for forming a resin layer (the first extruder for forming a resin layer and the second extruder for forming a resin layer). The co-extrusion die was an annular die having an annular extrusion outlet. The first extruder for forming a resin layer was connected to the co-extrusion die so that a resin layer could be formed on the inner surface side of a tubular laminated foam body described later, and the second extruder for forming a resin layer was connected to the co-extrusion die so that a resin layer could be formed on the outer surface side of a tubular laminated foam body described later.

[0105] [Table 1]

[0106] Examples 1 to 10 and Comparative Examples 1 to 8 (Melted material for forming foam layer) In each of Examples 1 to 10 and Comparative Examples 1 to 8, the resin constituting the foam layer, that is, the resin contained in the resin composition (A), is the resin (branched low-density polyethylene and linear low-density polyethylene) as shown in the raw material blending column of Tables 2, 3, and 4. For each of Examples 1 to 10 and Comparative Examples 1 to 8, under the conditions of the type and blending amount of raw material resin shown in the raw material blending column of "Foam layer (resin composition (A))" in Tables 2, 3, and 4, branched low-density polyethylene and linear low-density polyethylene were supplied to the first extruder of the tandem extruder as the resin contained in the resin composition (A) forming the foam layer, and further heated and melted in the first extruder and kneaded to form a resin melt. At this time, when forming the resin melt, a bubble regulator was also charged into the first extruder. The amount of the bubble regulator added was 1 part by mass per 100 parts by mass of branched low-density polyethylene. Fine Cell Master (product name PO217K) manufactured by Dainichiseika Chemicals Co., Ltd. was used as the bubble regulator. In Examples 1 to 10 and Comparative Examples 1 to 8, the shrinkage inhibitor was not fed to the tandem extruder, and therefore the foamed layer was a layer to which substantially no shrinkage inhibitor was added.

[0107] A physical foaming agent was supplied under pressure to the mixture (melt resin) of branched low-density polyethylene, linear low-density polyethylene, and cell control agent melted in the first extruder, and further kneaded in the first extruder. A melt for forming a foam layer was obtained in this manner. As the physical foaming agent, a mixed butane consisting of 70% by mass of normal butane and 30% by mass of isobutane was used. The amount of the physical foaming agent was as shown in the mixed butane amount column in Tables 2, 3, and 4.

[0108] The molten material for forming the foam layer obtained in the first extruder was transferred to the second extruder, where it was adjusted to a predetermined temperature (roughly the foam layer temperature (°C) in the resin temperature column of Tables 2, 3 and 4).

[0109] (Melted material for forming resin layer) In each of Examples 1 to 10 and Comparative Examples 1 to 8, the resin (branched low-density polyethylene and linear low-density polyethylene) shown in the raw material blending column of Table 2 or Table 4 is used as the polyethylene resin composition, which is the resin composition (B) constituting the resin layer. For each of Examples 1 to 10 and Comparative Examples 1 to 8, the branched low-density polyethylene and linear low-density polyethylene were supplied to the first extruder for forming the resin layer under the conditions of the type and blending amount of the raw material resin shown in the raw material blending column of "Resin layer (resin composition (B))" in Tables 2, 3 and 4, and further the shrinkage inhibitor was supplied in the blending amount shown in Tables 2, 3 and 4, and the mixture was heated, melted and kneaded in the first extruder for forming the resin layer to form a melt for forming the resin layer. In addition, a mixed butane consisting of 70% by mass of normal butane and 30% by mass of isobutane was used as the volatile plasticizer. The blending amount of the volatile plasticizer was as shown in Tables 2, 3 and 4. As the shrinkage inhibitor, the above-mentioned shrinkage inhibitor masterbatch was used.

[0110] The molten material for forming the resin layer formed in the second extruder for forming the resin layer was formed using the same raw resin and shrinkage prevention agent as the molten material for forming the resin layer formed in the first extruder for forming the resin layer for each of Examples 1 to 10 and Comparative Examples 1 to 8, and was formed using the same heating and melting conditions.

[0111] (Co-extrusion) The respective melts obtained by the extruder for forming a foam layer, the first extruder for forming a resin layer, and the second extruder for forming a resin layer are supplied to a co-extrusion die. At this time, inside the co-extrusion die, the respective melts are merged so that, from the inside, a layer of the melt for forming a resin layer formed by the first extruder for forming a resin layer, a layer of the melt for forming a foam layer, and a layer of the melt for forming a resin layer formed by the second extruder for forming a resin layer are laminated. Then, the laminated melts, in which the melt for forming a foam layer is sandwiched between the melts for forming a resin layer, are discharged from the extrusion port of the co-extrusion die, thereby obtaining a cylindrical laminated foam.

[0112] Regarding the manufacturing conditions during co-extrusion, the resin temperature of the melt for forming the resin layer and the discharge rate (kg / h) of the melt for forming the foam layer, and the resin temperature (extrusion resin temperature) (°C) when the melt is discharged are as shown in the resin layer column and foam layer column in the discharge rate column and resin temperature column of Tables 2, 3, and 4. Regarding the manufacturing conditions during co-extrusion, the melt lamination for forming the resin layer formed by the first extruder for forming the resin layer and the melt for forming the resin layer formed by the second extruder for forming the resin layer were both carried out using the conditions (discharge rate (kg / h) per side and resin temperature (°C) conditions) shown in the resin layer column of the manufacturing conditions column of Tables 2, 3, and 4. Therefore, the value in the resin layer column related to the discharge rate column indicates the discharge rate per side of the multilayer extruded foam sheet.

[0113] The production conditions in Tables 2, 3, and 4 indicate the production conditions applied to obtain a multi-layer extruded foam sheet having the highest closed cell ratio among the production conditions applied to obtain a multi-layer extruded foam sheet having the maximum moldable time range in the mold-1 described below. The appropriate foam layer resin temperature range (°C) in Tables 2, 3, and 4 indicates the range of the foam layer resin temperature during extrusion foaming (i.e., the extrusion foaming temperature) that can produce a multi-layer extruded foam sheet having a moldable time range of 4 seconds or more in the mold-1 described below.

[0114] A mandrel was inserted into the obtained cylindrical laminated foam, and the cylindrical laminated foam was cooled while being drawn along the mandrel. At this time, the cylindrical laminated foam was cut open to obtain multi-layer extruded foam sheets for each of Examples 1 to 10 and Comparative Examples 1 to 9. The drawing speeds of the cylindrical laminated foam are shown in Tables 2, 3 and 4.

[0115] In addition to the manufacturing conditions and take-up speeds described above, Tables 2, 3, and 4 also show the physical properties of the polyethylene resin composition that constitutes the resin layer, which is the resin composition (B), such as tensile elongation (%) at 23°C, tensile elongation (%) at 110°C, tensile strength (MPa) at 23°C, tensile strength (MPa) at 110°C, tensile product (%·MPa) at 23°C, tensile product (%·MPa) at 110°C, the ratio of tensile elongation at 110°C to tensile elongation at 23°C (tensile elongation (110°C) / tensile elongation (23°C)), the melting point (°C) of the resin composition (B), and the crystallization temperature (Tcr) (°C) of the resin composition (B). The tensile elongation (%) at each temperature, tensile strength (MPa) at each temperature, tensile product (MPa·%) at each temperature, (tensile elongation (110°C) / tensile elongation (23°C)), melting point and crystallization temperature of the polyethylene resin composition which is the resin composition (B) forming the resin layer were determined using the above-mentioned method, as described below. The composition of the polyethylene resin composition which is the resin composition (B) constituting the resin layer was the same as that shown in the "Raw material blend" column in Tables 2, 3 and 4, and the measurement sample was used.

[0116] The tensile elongation (%) at each temperature and the tensile strength (MPa) at each temperature of the resin composition (B) were specifically measured by the following method based on JIS K7161-1:2014.

[0117] (Tensile strength and tensile elongation at 23℃) Specifically, the resin composition (B) was first melt-kneaded in an extruder set to a maximum temperature of 180°C, and extruded to prepare a resin film having a thickness of 0.85±0.03 mm. A sheet piece having a dumbbell-shaped No. 1 shape as specified in 4.1 (shape and dimensions of test piece) of JIS K6251 was punched out from the film, and the sheet piece was used as a test piece to prepare a test piece. The test piece was left to stand for 24 hours in an atmosphere of 23°C and humidity of 50% to condition it. A universal material testing machine "Tensilon RTC-1250A" manufactured by A&D Co., Ltd. was used to perform a tensile test on the test piece at a test speed of 500 mm / min in an atmosphere of 23°C, and the tensile strength and tensile elongation of the test piece were measured. The above measurements were performed five times, and the arithmetic average values ​​of the tensile strength and tensile elongation obtained were taken as the tensile strength and tensile elongation of the polyethylene resin composition under the condition of 23°C. The tensile elongation is a value calculated based on the gauge length of a No. 1 dumbbell-shaped specimen (specifically, 40 mm).

[0118] (Tensile strength and tensile elongation at 110℃) The tensile strength and tensile elongation at 110°C were measured in the same manner as described in "Tensile strength and tensile elongation at 23°C", except that the universal testing machine thermostatic chamber "TLF-III-40-B" was attached to the universal material testing machine, the ambient temperature of the space in which the tensile test was performed was adjusted to 110°C ± 2°C, and the test piece was left to stand in that atmosphere for 30 seconds before the tensile test was performed.

[0119] The crystallization temperature of the polyethylene resin composition of the resin layer was measured based on a DSC curve measured using a heat flux differential scanning calorimeter in accordance with JIS K7121:2012. Specifically, first, the test piece was heated from 23°C to 200°C at a heating rate of 10°C / min, and then kept at this temperature for 10 minutes. Then, the test piece was cooled to 30°C at a cooling rate of 10°C / min to perform heat flux DSC (i.e., differential scanning calorimetry), and the DSC curve during the cooling process was obtained. The DSC curve was obtained as a graph with the horizontal axis representing temperature (°C) and the vertical axis representing heat flow (W / g). The apex temperature of the exothermic peak appearing at the highest temperature among the exothermic peaks appearing in the obtained DSC curve was taken as the crystallization temperature Tcr of the polyethylene resin composition. As the measuring device, a heat flux differential scanning calorimeter (manufactured by TA Instruments, Inc., "Device name: DSC Q1000") was used.

[0120] In Tables 2, 3, and 4, the melting point of the resin composition (A) and the crystallization temperature (Tcf) derived from the branched low density polyethylene (LDPE) contained as the main component in the resin composition (A) are listed in the melting point column and the crystallization temperature column in the foam layer column, respectively, as the physical properties of the resin composition (A) constituting the foam layer. The melting point of the resin composition (A) and the crystallization temperature derived from the branched low density polyethylene that is the main component of the resin composition (A) were determined using the method described above.

[0121] Furthermore, the crystallization temperature difference (°C) is shown in Tables 2, 3, and 4. The crystallization temperature difference is calculated as the value ([Tcr-Tcf]) obtained by subtracting the crystallization temperature (Tcf) derived from the branched low density polyethylene contained in the foamed layer from the crystallization temperature (Tcr) of the polyethylene resin composition in the resin layer.

[0122] [Table 2]

[0123] [Table 3]

[0124] [Table 4]

[0125] The multi-layer extruded foam sheets obtained in each of Examples 1 to 10 and Comparative Examples 1 to 8 are laminated foam sheets having a structure in which a resin layer is provided on both sides of a foam layer. The ratio (mass%) of the insoluble matter of the multi-layer extruded foam sheets measured by hot xylene extraction was 0. In other words, both the foam layer and the resin layer were non-crosslinked.

[0126] The total thickness (mm) of the multi-layer extruded foam sheet was measured for each of Examples 1 to 10 and Comparative Examples 1 to 8. The method for measuring the total thickness of the multi-layer extruded foam sheet was as described above. The results are shown in Tables 5, 6, and 7.

[0127] The basis weights of the foam layer and the resin layer of the multi-layer extruded foam sheet were specified as shown in Tables 5, 6, and 7. In Tables 5, 6, and 7, the mandrel surface side column of the resin layer (resin layer on the mandrel surface side) lists the basis weight of the resin layer derived from the molten material for forming the resin layer formed in the first extruder for forming the resin layer, and the outer surface side column of the resin layer (resin layer on the outer surface side) lists the basis weight of the resin layer derived from the molten material for forming the resin layer formed in the second extruder for forming the resin layer.

[0128] The basis weight of each layer is calculated from the basis weight (kg / m2) calculated from the amount of molten material discharged (discharge rate), the take-up speed of the multi-layer extruded foam sheet, and the width of the multi-layer extruded foam sheet in the manufacturing process of the multi-layer extruded foam sheet using the following formulas (3) and (4). 2 ) to g / m 2 The unit was converted to 1000 units. The total basis weight of the multi-layer extruded foam sheet is also shown in Tables 5, 6, and 7. The total basis weight of the multi-layer extruded foam sheet is the sum of the basis weights of the foam layer and the resin layer.

[0129]

number

number

[0130] In the above formulas (3) and (4), X1 is the discharge amount of the molten material for forming the foam layer (unit: kg / hour), X2 is the discharge amount of the molten material for forming the resin layer per side (unit: kg / hour), L is the take-up speed of the multi-layer extruded foam sheet (unit: m / hour), and W is the width of the multi-layer extruded foam sheet (unit: m).

[0131] In addition, the extrusion volume of the molten material for forming the resin layer was the same for both the molten material for forming the resin layer formed by the first extruder for forming the resin layer and the molten material for forming the resin layer formed by the second extruder for forming the resin layer.

[0132] In addition, for each of Examples 1 to 10 and Comparative Examples 1 to 8, the basis weight (g / m) of the entire multi-layer extruded foam sheet was 3 ) and the total thickness (mm), the apparent density (kg / m 3 ) was determined. Furthermore, the closed cell ratio (%) of the multi-layer extruded foam sheet obtained in Example 1 was determined. The closed cell ratio was determined using the method described above. The results are shown in Tables 5, 6, and 7.

[0133] The multi-layer extruded foam sheets obtained in each of Examples 1 to 10 and Comparative Examples 1 to 8 were evaluated for thermoformability and rigidity as follows.

[0134] (Evaluation of thermoformability) A multi-layer extrusion foam sheet was thermoformed using a molding machine and a mold. Two types of molds were prepared. In Tables 5, 6, and 7, the two types of molds are referred to as mold-1 and mold-2, respectively. For both mold-1 and mold-2, molds corresponding to a shape (shape of molded body) in which four box-shaped parts, each of which is rectangular in plan view and has an open upper surface, are arranged in a line in the width direction (width direction of the box-shaped part) were used. Mold-1 was set to a shape corresponding to a molded body having a bottom length of 242 mm and a depth of 23.5 mm (expansion ratio 1.78) of each box-shaped part. Mold-2 was set to a shape corresponding to a molded body having a bottom length of 242 mm and a depth of 27 mm (expansion ratio 2.02) of each box-shaped part. The bottom length of the box-shaped part indicates the length in the longitudinal direction of the box-shaped part. Thermoforming with Mold-2 is more difficult than thermoforming with Mold-1 because of the higher expansion ratio. Thermoforming was performed by heating the multi-layer extruded foam sheet and then shaping it in a mold. The conditions for thermoforming were a heater temperature of 320°C used to heat the multi-layer extruded foam sheet and a mold temperature of 60°C.

[0135] (Determining the time range in which molding is possible) The heating time of the multi-layer extruded foam sheet was used as a variable to determine the range of time within which it was determined that the sheet could be molded (moldable time range (seconds)). The results are shown in Tables 5, 6, and 7.

[0136] The judgement of whether or not the product was moldable was carried out by the following method: First, the molded product obtained by thermoforming was visually inspected for the presence or absence of breakage in the molded product, and the molding rate (%) was determined.

[0137] (Excipient rate) The shaping rate (%) was determined as follows: The shaping rate (%) was determined as the value obtained by multiplying the ratio of the depth of the molded body (mm) to the depth of the mold (mm) [(depth of molded body) / (depth of mold)] by the ratio of the length of the bottom part of the molded body (mm) to the length of the bottom part of the mold (mm) [(length of bottom part of molded body) / (length of bottom part of mold)]] by 100 (a value calculated by the formula [(depth of molded body) / (depth of mold)]×[(length of bottom part of molded body) / (length of bottom part of mold)]×100).

[0138] The criteria for determining whether or not a moldable product was moldable were that the molded product was moldable when no cracks were observed in the molded product and the moldability was 80% or more.

[0139] Based on the results of the moldable time range (seconds), a comprehensive evaluation of thermoformability was performed according to the following criteria.

[0140] ⊚ (Very good): The thermoforming time was 6 seconds or more for both mold-1 and mold-2. ◯ (Good): The thermoforming time for mold-1 is 6 seconds or more, and the thermoforming time for mold-2 is less than 6 seconds. Δ (slightly poor): The thermoforming time for mold-1 was more than 0 seconds and less than 6 seconds, and moldability was not possible for mold-2. × (bad): molding was not possible with either mold-1 or mold-2.

[0141] As properties of the molded article obtained by thermoforming the multi-layer extruded foam sheet, the wall thickness and rigidity of the molded article were measured and evaluated as follows.

[0142] (Thickness of molded body) Regarding the measurement of the thickness of the molded article, the thickness (mm) of the molded article having the highest closed cell ratio among the molded articles obtained by thermoforming the multi-layer extruded foam sheet using "Mold-1" in evaluating "thermoformability" in each of the above-mentioned Examples and Comparative Examples was measured.

[0143] As shown in Tables 5, 6, and 7, the thickness (mm) of the side part and the thickness (mm) of the bottom part of the molded body were measured as the thickness (mm) of the molded body. The bottom part of the molded body is the part corresponding to the box-shaped bottom part described above, and the side part of the molded body is specified as the part rising from the outer periphery of the bottom part of the molded body. The thickness (mm) of the bottom part of the molded body was determined as the thickness (mm) at a position selected approximately near the center of the bottom part. The thickness (mm) of the side part of the molded body was determined as the thickness (mm) at a position selected approximately near the middle between the boundary between the bottom part and the side part and the tip of the side part.

[0144] In thermoforming of a multi-layer extruded foam sheet, the multi-layer extruded foam sheet to be thermoformed is stretched and shaped into a predetermined shape. Therefore, the thickness of the molded product is thinner than the thickness of the multi-layer extruded foam sheet before molding. The thickness reduction rate (%) of each measurement point (mm) of the bottom and side parts of the obtained molded product was calculated by the following formula (5). The results are shown in Tables 5, 6, and 7. It can be seen that the smaller the thickness reduction rate, the more the thickness of the multi-layer extruded foam sheet before molding can be maintained during thermoforming.

[0145]

number

[0146] In addition, in Tables 5, 6, and 7, the value obtained by subtracting the thickness of the bottom portion from the thickness of the side wall portion is shown in the ``Side wall thickness - Bottom portion thickness'' column of Tables 5, 6, and 7 as an indicator of the uniformity of thickness for each part of the molded body.

[0147] (Rigidity evaluation) The evaluation of rigidity was carried out based on the measurement of compressive strength of the molded body. In the measurement of compressive strength of the molded body, the molded body with the highest closed cell ratio among the molded bodies obtained by thermoforming the multi-layer extruded foam sheet using "Mold-1" in the evaluation of "thermoformability" in each of the above-mentioned Examples and Comparative Examples was used as the test body. The thicknesses of the molded bodies used as the test bodies are shown in Tables 5, 6, and 7.

[0148] The compressive strength of the molded body was measured by placing the bottom of the test specimen facing upward and the open side facing downward, placing an indenter with R=5 on the outer surface of the bottom side, and crushing the test specimen downward with the indenter at a speed of 10 mm / min. The load at the time when the indenter was displaced downward by 10 mm was determined, and the magnitude of the load was taken as the 10 mm compressive load (N). The measurement results are shown in Tables 5, 6, and 7.

[0149] For each of Examples 1 to 8 and Comparative Examples 1 to 6, a rigidity evaluation (evaluation of compact compressive strength) was performed based on the 10 mm compressive load (N) according to the following criteria. The results are shown in Tables 5 and 6.

[0150] ○ (Good): 10mm compressive strength is 1.20N or more. × (Poor): 10mm compressive strength is less than 1.20N.

[0151] For each of the molded articles in Examples 9 to 10 and Comparative Examples 7 to 8, the basis weight or thickness of the multi-layer extruded foam sheet was set to be small. Therefore, the value of the 10 mm compression load (N), which is the standard for evaluating the rigidity (evaluation of the compressive strength of the molded article), was changed as follows, taking into account the basis weight and thickness of the multi-layer extruded foam sheet. The results are shown in Table 7.

[0152] ○ (Good): 10mm compressive strength is 1.00N or more. × (Poor): 10mm compressive strength is less than 1.00N.

[0153] [Table 5]

[0154] [Table 6]

[0155] [Table 7] [Explanation of symbols]

[0156] CP1, CP2: Peak CPR1, CPR2: Peak

Claims

1. A polyethylene-based resin multi-layer extrusion foam sheet for thermoforming, comprising a polyethylene-based resin layer laminated on at least one side of a polyethylene-based resin foam layer mainly composed of a branched low-density polyethylene, wherein the polyethylene-based resin composition constituting the polyethylene-based resin layer has a crystallization temperature Tcr of 108° C. or lower, The polyethylene-based resin composition constituting the polyethylene-based resin layer has a product of tensile strength (MPa) and tensile elongation (%) at 110°C of 1,300 (MPa·%) or more.

2. the difference [Tcr-Tcf] between the crystallization temperature Tcf of the branched low density polyethylene and the crystallization temperature Tcr of the polyethylene resin composition is 0°C or more and 10°C or less; The multi-layer extruded polyethylene resin foam sheet for thermoforming according to claim 1 .

3. The thickness of the thermoforming polyethylene-based resin multi-layer extruded foam sheet is 1 mm or more and 3.5 mm or less. The multi-layer extruded polyethylene resin foam sheet for thermoforming according to claim 1 or 2.

4. The basis weight of the thermoforming polyethylene resin multi-layer extruded foam sheet is 150 g / m 2 3. The extruded polyethylene resin multi-layer foam sheet for thermoforming according to claim 1 or 2, wherein:

5. The polyethylene resin composition contains a linear low-density polyethylene. The multi-layer extruded polyethylene resin foam sheet for thermoforming according to claim 1 or 2.

6. the polyethylene-based resin composition is mainly composed of a mixed resin of linear low-density polyethylene and branched low-density polyethylene, and the mass ratio of the linear low-density polyethylene to the branched low-density polyethylene in the polyethylene-based resin composition is 90:10 to 30:70; The multi-layer extruded polyethylene resin foam sheet for thermoforming according to claim 1 or 2.

7. the ratio of the tensile elongation (%) of the polyethylene resin composition at 110°C to the tensile elongation (%) of the polyethylene resin composition at 23°C is 0.3 or more; The multi-layer extruded polyethylene resin foam sheet for thermoforming according to claim 1 or 2.

8. the polyethylene-based resin composition contains one or more shrinkage inhibitors selected from the group consisting of fatty acid esters, aliphatic amines, and fatty acid amides, the blending amount of the shrinkage inhibitor is 0.7 parts by mass or more and 3 parts by mass or less per 100 parts by mass of the polyethylene-based resin constituting the polyethylene-based resin composition, and the polyethylene-based resin foam layer is substantially free of one or more shrinkage inhibitors selected from the group consisting of fatty acid esters, aliphatic amines, and fatty acid amides. The multi-layer extruded polyethylene resin foam sheet for thermoforming according to claim 1 or 2.

9. the product of tensile strength (MPa) and tensile elongation (%) of the polyethylene-based resin composition at 110°C is 1600 or more, and the polyethylene-based resin foam layer and the polyethylene-based resin layer are substantially free of one or more shrinkage inhibitors selected from the group consisting of fatty acid esters, aliphatic amines, and fatty acid amides; The multi-layer extruded polyethylene resin foam sheet for thermoforming according to claim 1 or 2.

10. The polyethylene resin composition contains a copolymer of ethylene and an α-olefin having 8 carbon atoms as a linear low-density polyethylene. The multi-layer extruded polyethylene resin foam sheet for thermoforming according to claim 1 or 2.

11. 3. The multi-layer extruded polyethylene resin foam sheet for thermoforming according to claim 1, wherein the multi-layer extruded polyethylene resin foam sheet for thermoforming has a closed cell content of 40% or more.

12. 3. A molded article obtained by thermoforming the multi-layer extruded polyethylene resin foam sheet for thermoforming according to claim 1 or 2.

13. A molten material for forming a foam layer obtained by kneading a branched low-density polyethylene and a physical foaming agent and a molten material for forming a resin layer obtained by melt-kneading a polyethylene-based resin composition are co-extruded, A method for producing a multi-layer extruded polyethylene resin foam sheet for thermoforming, in which a polyethylene resin layer is laminated on at least one side of a polyethylene resin foam layer, comprising the steps of: The crystallization temperature Tcr of the polyethylene resin composition is 108° C. or lower, The polyethylene resin composition has a product of tensile strength (MPa) and tensile elongation (%) at 110° C. of 1,300 (MPa·%) or more.

Citation Information

Patent Citations

  • Polyethylene resin multilayer foamed sheet and molded form thereof

    JP2013035177A